2023
DOI: 10.3389/fgene.2023.1241912
|View full text |Cite
|
Sign up to set email alerts
|

BCR::ABL1-negative myeloproliferative neoplasms in the era of next-generation sequencing

Aleksandra Mroczkowska-Bękarciak,
Tomasz Wróbel

Abstract: The classical BCR::ABL1-negative myeloproliferative neoplasms such as polycythemia vera (PV), essential thrombocythemia (ET), and myelofibrosis (MF) are clonal diseases with the presence of characteristic “driver mutations” in one of the genes: JAK2, CALR, or MPL. The search for mutations in these three genes is required for the diagnosis of MPNs. Nevertheless, the progress that has been made in the field of molecular genetics has opened a new era in medicine. The search for additional mutations in MPNs is hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
1
3
0
Order By: Relevance
“…A query of the American Association for Cancer Research (AACR) Project GENIE public database in cBioportal [32] found 299 samples from 202 cases documented as PMF (https://genie.cbioportal.org/study?id=6562046bb01fff74fbb6c576 (accessed on 25 November 2023)). In these 299 samples, in addition to JAK2 (44.8%), CALR (14.7%), and MPL (9.4%) mutations, the prevalence of other mutations is similar to those reported by other studies [29,31,33,34]. Table 1 lists the prevalence of relatively frequent non-driver mutations and the most common mutations or mutation types cataloged in the GENIE database.…”
Section: Additional Mutationssupporting
confidence: 77%
See 1 more Smart Citation
“…A query of the American Association for Cancer Research (AACR) Project GENIE public database in cBioportal [32] found 299 samples from 202 cases documented as PMF (https://genie.cbioportal.org/study?id=6562046bb01fff74fbb6c576 (accessed on 25 November 2023)). In these 299 samples, in addition to JAK2 (44.8%), CALR (14.7%), and MPL (9.4%) mutations, the prevalence of other mutations is similar to those reported by other studies [29,31,33,34]. Table 1 lists the prevalence of relatively frequent non-driver mutations and the most common mutations or mutation types cataloged in the GENIE database.…”
Section: Additional Mutationssupporting
confidence: 77%
“…other studies [29,31,33,34]. Table 1 lists the prevalence of relatively frequent non-driver mutations and the most common mutations or mutation types cataloged in the GENIE database.…”
Section: Additional Mutationsmentioning
confidence: 99%
“…Figure 2 provides a comprehensive view of the gene mutation landscapes within each patient with MN, considering the WHO-HAEM5 reclassified disease categories. [ 4 , 12 ] Genes were further organized into distinct functional groups, adapted from the relevant literature. [ 13 ] When interpreting gene mutation status, it is worth noting that in addition to pathogenic mutations, some mutations of uncertain significance, often with multiple coexisting mutations, are often found in MPN (Table 3 , Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Philadelphia-negative (Ph−) chronic myeloproliferative neoplasms are clonal diseases that arise from a pluripotent hematopoietic stem cell. They include, among others, polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) [1].…”
Section: Introductionmentioning
confidence: 99%